Torsional vibrations of nonhomogeneous magnetostrictive elastic circular cylinder - A. N. Abd-Alla; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with the torsional vibrations of a nonhomogeneous magnetostrictive elastic cylinder. The cylinder is subjected to the action of a circumferential magnetic field produced by an axial current of constant density and the deformation of a magnetostrictive cylinder is produced by a constant longitudinal magnetic field. The frequency equation is determined, and the displacement and stress components are numerically calculated with graphical presentations.